Pendampingan Pembuatan Media Pembelajaran Bangun Ruang dengan Memanfaatkan Teknologi Augmented Reality pada Guru Matematika SMP di Kota Serang - Ayuningtyas, Vidya; Ginanjar, Gigin; Nabila, Elsa; Aisah, Arsi (EMPOWERMENT: Journal of Community Practice, 2025)
Rapid changes in the world of technology require updates in learning approaches, especially in the field of mathematics which is often difficult to understand because of its abstract nature, such as material related to three-dimensional shapes. However, conventional methods are still dominant in the classroom, thus limiting students' understanding. One alternative that can answer this challenge is the use of Augmented Reality (AR). This community service activity was carried out together with the MGMP Mathematics SMP teacher forum in Serang City and aims to provide teachers with knowledge and skills in applying AR to mathematics learning for the material of Spatial Buildings. The implementation process involves four stages, namely identification of initial conditions, preparation of activity plans, implementation of training, and evaluation of results. A total of 67 teachers who attended from the invitation (socialization) from various class levels actively participated in this activity. The results showed an increase in teacher knowledge and abilities in integrating AR technology into a more interesting and meaningful learning process. The responses given by participants also showed high enthusiasm for the sustainability of similar programs. Therefore, follow-up programs such as intensive mentoring and development of AR-based teaching materials that are in accordance with the needs of the national curriculum are highly recommended to support the transformation of mathematics learning in schools.